1995
DOI: 10.1136/bjo.79.11.1042
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of tear clearance rate and fluorophotometric assessment of tear turnover.

Abstract: Participants and methods SUBJECTSThe study group comprised 34 healthy individuals (mean age 58-4 (SD 14-7) years, ranging from 22 to 84 years). Tear turnover was determined in 55 eyes of the subjects. They were examined by slit-lamp microscope without fluorescein to ensure there were no corneal epithelial lesions. Subjects who wore contact lenses, had ocular abnormalities, or systemic diseases related to tear secretion were excluded. Informed consent was obtained from all subjects before the study. INSTRUMENTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 11 publications
1
43
0
Order By: Relevance
“…ST V may have higher values in the first minutes and diminish gradually during the tests (22)(23)(24) . ST V can also be a parameter for tear volume in humans, but further research should be carried out.…”
Section: Chartmentioning
confidence: 99%
“…ST V may have higher values in the first minutes and diminish gradually during the tests (22)(23)(24) . ST V can also be a parameter for tear volume in humans, but further research should be carried out.…”
Section: Chartmentioning
confidence: 99%
“…This sequence was followed by a period of 10 minutes of spontaneous blinking prior to any experimental procedure. This is in keeping with the approach of Xu and Tsubota 36 who performed the anaesthetic Schirmer test at an interval of five minutes after drop instillation and without prior removal of tear fluid from the conjunctival sac.…”
Section: Instillation Of Eye Dropsmentioning
confidence: 95%
“…13,14 It is suggested that there is a strong association of delayed tear clearance with intrinsically and extrinsically generated ocular surface inflammation, and that delayed tear clearance constitutes the basis for creating a vicious cycle to perpetuate the underlying insults derived from these inflammatory stimuli. 15 A delay in tear clearance might theoretically increase the immunoglobulin and/or leukotriene concentrations in the tear film and further increase the incidence of lens protein deposition and associated inflammation.…”
mentioning
confidence: 99%